(3GSJQGJjLjGJ hYedjGJ GdEOGQIs - (3YHO GdgGOj GHQGgje(B, (3GdedjLjs ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2002)
(3GdeONd dOQGSI GdEOGQI GdYGeI , efGgL heOGNd OQGSI GdEOGQI GdYGeI , GdeUWdMGJ hGdeaGgje GdYdejI ddEOGQI GdefXeI , GdEOGQI hXGFagG hYedjGJgGs
(3GdeQGLY U(B.349s
Keywords: (3GdEOGQI GdYGeIs